Safety of FFR-guided revascularisation deferral in Anatomically prognostiC diseasE (FACE: CARDIOGROUP V STUDY): A prospective multicentre study. (1st November 2018) - Barbero, Umberto; D'Ascenzo, Fabrizio; Campo, Gianluca; Kleczyński, Paweł; Dziewierz, Artur; Menozzi, Mila; Jiménez Díaz, Victor A.; Cerrato, Enrico; Raposeiras-Roubín, Sergio; Ielasi, Alfonso; Rognoni, Andrea; Fineschi, Massimo; et al.
Abstract: Background: FFR-guided coronary intervention is recommended for patients with intermediate stenoses. However, concerns exist with this approach in anatomically prognostic disease. Methods: In this prospective, multicentre study, we consecutively enrolled patients found to have FFR negative lesions in anatomically significant sites: left main; proximal LAD; last remaining patent vessel; and multiple vessels with concomitant impaired left ventricular systolic function (EF < 40%). As per recommendation, revascularisation was deferred, and patients included into a registry. The primary endpoint was MACE (death, myocardial infarction and unplanned target lesion revascularization). Secondary endpoints were the above individual components. Subgroup analyses were performed for clinical presentation (stable vs. ACS), localization of lesion (ostial vs. non ostial) and renal function. Results: The registry included 292 patients with 297 deferred stenoses. After 1-year, the primary endpoint occurred in 5% of patients, mainly driven by TLR (2.7%). Cardiovascular death occurred in 0.8% and AMI in 0.8%. During a follow-up of 22.2 ± 11 months, MACE occurred in 11.6%. Cardiovascular death occurred in 1.8% and AMI in 2.1%. After multivariate analysis, impaired renal function (OR 1.99; CI 95% 1.74–5.41; p = 0.046) and ostial disease (OR 2.88; CI 95% 1.04–7.38; p = 0.041) were found to be predictors of MACE. Impaired renal function also predicted TLR (OR 2.43; CI 95% 1.17–5.02; p = 0.017). Conclusion: FFR-guided revascularisation deferral is safe in the majority of anatomically prognostic disease. However, further evaluation is required in the risk stratification of those patients with ostial disease and renal disease. Registered on ClinicalTrials, NCT02590926 . Graphical abstract: Highlights: The registry of stenosis carrying high prognostic impact included 292 patients with 297 deferred stenosis. FFR-guided revascularisation deferral is safe in this registry: after 1-year, the primary endpoint occurred in 5% of patients, mainly driven by TLR (2.7%). Further evaluation is required in the risk stratification of those patients with ostial disease and renal disease.